Perceptions and Opinions Regarding the Reintroduction of Eurasian Lynx to England: A Preliminary Study - Megan Pearson; Angus I. Carpenter (Conservation, 2025)
Globally, national governments have committed to restoring their native biodiversity, which can include the reintroduction of species. Amassing public support can prove difficult when the species is considered a contestable species, such as the Eurasian lynx, Lynx lynx, within the UK. Using an e-questionnaire widely distributed across social media platforms enabled the investigation of public perceptions regarding any proposed lynx reintroduction to England. The majority of the public generally supported the idea of a lynx reintroduction to England. Further investigation by societal groups allowed for greater and more detailed knowledge of perceptions, attitudes, and potential barriers to the potential reintroduction of this contestable species. There were varying opinions both negative and positive, between distinct societal groups, while respondent statements highlighted justifications for their positions. A closer investigation identified specific areas for educational efforts and engagement prior to any public consultation. Many negative opinions were based on either a lack of knowledge or misinformation, which highlighted where educational efforts should be targeted. Misinformation appeared rife within the farmer, vet, and wildlife photography groups. The study highlighted that applying both macro- and micro-scale analyses greatly benefits the identification, detail, and specific issues that need to be addressed, therefore enabling more efficient planning of relevant actions to address concerns before proceeding with such a proposal, especially at a time when funding is limited.